The security of human-computer interaction by speech - Bispham, MK (2020)
This thesis investigates the security issues associated with human-computer interaction by speech, focussing on the context of voice-controlled digital assistants. The security of human-computer interaction by speech has become increasingly important as use of voice control has become more widespread. The research questions addressed in the thesis are whether the speech interface presents particular vulnerabilities that are not relevant to other types of interfaces, and, if so, what these vulnerabilities are and how attacks exploiting them can be defended. Based on a critical review of prior work, it is argued that the speech interface does represent a new attack surface with specific security vulnerabilities that have not as yet been comprehensively studied. These vulnerabilities arise both in relation to the inherently open nature of the speech interface, as well in relation to unintended functionality in the technologies implemented in voice-controlled systems to imitate human speech and language processing.